ANALISIS WACANA KRITIS PENDEKATAN TEUN A. VAN DIJK TERHADAP BERITA “PMK MEWABAH, MUI JATENG BEBERKAN SYARAT SAH HEWAN KURBAN” - Dinni Sukma Haryanti; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
Towards the celebration of Eid al-Adha in 2022, there was a lot of discussion in the media, both print and online, about the outbreak of Foot and Mouth Disease (FMD) in livestock. The purpose of this research is (1) to describe the text structure of the news according to the critical discourse analysis approach by Teun A. Van Dijk, and (2) to describe the characteristics of critical discourse analysis in the news text. This study employed a qualitative descriptive research method using Teun Van Dijk's Critical Discourse Analysis model. The data source for this research was a news article titled